Investigation of passive bearing for biomedical applications - Goh, Yong Seng (2016)
This project seeks to investigate the effect of varying the cross-sectional parameters of the groove of a hydrodynamic bearing on its positive differential pressure generation. It is desired to obtain a maximum positive differential pressure generation at a fluid film thickness of 0.2mm and above in order to minimize the power required to drive the impeller for hydrodynamic lift. Previous simulations and experimental results were studied to identify regions of poor pressure generation so that improvements can be made. Preliminary investigations suggest that higher positive pressure generation occurs along the outer spiral compared to the inner spiral. This phenomenon is due to the collision of fluid particles against the groove wall at the outer spiral as a result of the rotational direction of the bearing. The study of Reynolds equation suggests that variation in depth of the bearing is important to obtain desired pressure generation along the flow. The design of the novel bearings kick-off with the modeling of the fluid domain using SolidWorks 2015. This was followed by a series of Computational Fluid Dynamics (CFD) simulations of the novel designs. The key things to take note while using these software are provided for the reference of subsequent users. New design features were incorporated into a previously optimized hydrodynamic bearing which exhibited promising positive differential pressure generation performance using the design concept of varied spiral groove angle on the outer spiral of Spiral Groove Bearings (SGB). The new design features include increasing the surface area of the groove by having a slanted groove bottom, varying the groove depth and varying the cross-sectional shapes from the inlet to the outlet of the groove. Other than generating positive differential pressure, these design features contribute to the fluid flow by delivering a scooping or propelling effect to the fluid particles. The detailed observations and conclusions are presented in this study. Experimental results were obtained on four newly fabricated bearings. These four bearings were chosen as they exhibited the greatest potential for generating positive differential pressure at 0.2mm film thickness based on previous studies. Current experimental results show that positive differential pressure generation is achievable for all except Optimized K15 at a rotational velocity of 1500rpm. However, at 2100rpm, all newly fabricated bearings exhibited negative differential pressure generation. By comparing the theoretical calculations, simulation and experimental results of Optimized K15 bearing, it was observed that the simulation results closely resemble the theoretical calculation predicted using modified Muijderman equations. However, both CFD simulation and theoretical predictions differed significantly from the experimental results. Thus, compensation factor was introduced to account for the discrepancies in these results. For the I14O1420 series of bearings, CFD simulations were unable to accurately predict the values for the corresponding experiments. Hence, possible explanations were presented in this study. Acronyms such as Optimized K15 are explained in detail in this report.